Gramsci and the critical tradition: Social Study Of Education - Suárez, Daniel (Education Policy Analysis Archives, 2004)
In this analysis, I review two of the most significant contributions of Antonio Gramsci to the sociological analysis of schooling. On the one hand, a great part of his work suggests reformulation of critical educational theory. On the other hand, Gramsci's contributions allow for a thorough rethinking of traditional ways of conceptualizing the schooling system and the curriculum. In this article, I contend that many works about Gramsci's theoretical contributions in education have not had a critical examination, and I hope that my suggestions for a re-reading of his works will not fail in the same way. Moreover, I want to contribute to the further understanding of Gramsci's influence in education in two specific ways: firstly, by using Gramsci's frameworks for the understanding of the social practices that shape the school as a modern institution; secondly, in conceptualizing these social practices which define the cultural and formative experiences at school. To do so, I propose that it will be necessary not to deify Gramsci´s thought but to develop it from a holistic perspective in order to visualize the implications of his concepts and categories.